The Writer as an Acrobat: Deleuze and Guattari on the Relation between Philosophy and Literature (and How Kierkegaard Moves in-between) - Daphne Giofkou (Transnational Literature, 2015)
Throughout his work, Deleuze not only draws on literature in order to address philosophical problems but he also maps out the “mobile relations” between philosophy and literature. After an initial overview, I will focus primarily on plateau “1874: Three Novellas or ‘What happened?’” of A Thousand Plateaus (1980), a book co-authored with Guattari. Through analyzing three novellas by Henry James, F. Scott Fitzgerald, and Pierrette Fleutiaux, Deleuze and Guattari develop here the particular way that novella as a literary genre (a) relates to secrecy and (b) combines the three lines: the line of rigid segmentarity, the line of supple segmentarity, and the line of flight. I argue that novella-time could be extended beyond the limits of the literary genre ‘novella’. To this end, I propose a reading of Kierkegaard’s novella Repetition (1843) and selected entries from his Journals, the suicidal note of the Greek neo-romantic poet Costas Karyotakis (1896-1928) as well as Nikos Gabriel Pentzikis’s prose Mother Thessaloniki (1970). I conclude that time and the transcendence of the given linear arrangement of past, present, and future stands out as a common problematic of philosophy, literature, and life.